Appsmart Learning Application Based on PBL Model Assisted by Articulate Storyline 3 on Electrical Energy Material - Sukrisnawan, I Ketut; I Gede Margunayasa; Gusti Ayu Putu Sukma Trisna (Jurnal Edutech Undiksha, 2023)
Problem-solving skills are important for students, so these problem-solving skills should be implemented early. Students feel bored in class, so students should be more focused on receiving the material presented by the teacher. The research aims to create an Appsmart learning application based on the PBL model assisted by Articulate Storyline 3. This type of research is Research and Development (R & D). The subjects of this research were 4 experts, 3 teachers, and 12 students. The object of this research is Appsmart based on the PBL model. This research uses a pre-experimental design, a one-shot case study. The data collection methods used were questionnaires and tests. The data analysis techniques used are quantitative descriptive and qualitative descriptive. The material and media experts' assessment results obtained an assessment score of 0.90 with very high validity qualifications. Based on the results, practicality by teachers was 92.36%, and practicality by students was 90%. The research conclusion is that the Appsmart learning application based on the PBL model effectively increases understanding of science concepts in Electrical Energy materials. The implications of this research can improve the quality of education by the learning objectives achieved.